Direct Comparison of 2 Rule-Out Strategies for Acute Myocardial Infarction: 2-h Accelerated Diagnostic Protocol vs 2-h Algorithm. (6th January 2020) - Wildi, Karin; Cullen, Louise; Twerenbold, Raphael; Greenslade, Jaimi H; Parsonage, William; Boeddinghaus, Jasper; Nestelberger, Thomas; Sabti, Zaid; Rubini-Giménez, Maria; Puelacher, Christian; Cupa, Janosch; Schumacher, Lukas; et al.
Abstract: BACKGROUND: We compared 2 high-sensitivity cardiac troponin (hs-cTn)-based 2-h strategies in patients presenting with suspected acute myocardial infarction (AMI) to the emergency department (ED): the 2-h accelerated diagnostic protocol (2h-ADP) combining hs-cTn, electrocardiogram, and a risk score, and the 2-h algorithm exclusively based on hs-cTn concentrations and their absolute changes. METHODS: Analyses were performed in 2 independent diagnostic cohorts [European Advantageous Predictors of Acute Coronary Syndrome Evaluation (APACE) study, Australian–New Zealand 2-h Accelerated Diagnostic Protocol to Assess patients with chest Pain symptoms using contemporary Troponins as the only biomarker (ADAPT) study] employing hs-cTnT (Elecsys) and hs-cTnI (Architect). The final diagnosis was adjudicated by 2 independent cardiologists. RESULTS: AMI was the final diagnosis in 16.5% (95% CI, 14.6%–18.6%) of the 1372 patients in APACE, and 12.6% (95% CI, 10.7%–14.7%) of 1153 patients in ADAPT. The negative predictive value (NPV) and sensitivity for AMI were very high and comparable with both strategies using either hs-cTnT or hs-cTnI in both cohorts (all statistical comparisons nonsignificant). The percentage of patients triaged toward rule-out was significantly lower with the 2h-ADP (36%–43%) vs the 2-h algorithm (55%–68%) with both assays and in both cohorts ( P < 0.001). The sensitivity of the 2h-ADP was higher for 30-day major adverse cardiovascular events. CONCLUSIONS: Both algorithms provided very high and comparable safety as quantified by the NPV and sensitivity for AMI and major adverse cardiac events (MACE) at 30 days in patients triaged toward rule-out, although sensitivity for MACE at 30 days was lower with both algorithms in cohort 2. Although the 2-h algorithm was more efficacious, not all patients ruled out for AMI by this algorithm were appropriate candidates for early discharge. The 2h-ADP seems superior in the selection of patients for early discharge from the ED. CLINICAL TRIAL REGISTRATION: APACE: http://clinicaltrials.gov/show/NCT00470587 ADAPT: Australia-New Zealand Clinical Trials Registry ACTRN12611001069943